Deltas in the Anthropocene - Nicholls, Robert J.; Adger, W. Neil; Hutton, Craig W.; Hanson, Susan E. (Springer Nature, 2020)
The Anthropocene is the human-dominated modern era that has accelerated social, environmental and climate change across the world in the last few decades. This open access book examines the challenges the Anthropocene presents to the sustainable management of deltas, both the many threats as well as the opportunities. In the world's deltas the Anthropocene is manifest in major land use change, the damming of rivers, the engineering of coasts and the growth of some of the world's largest megacities; deltas are home to one in twelve of all people in the world. The book explores bio-physical and social dynamics and makes clear adaptation choices and trade-offs that underpin policy and governance processes, including visionary delta management plans. It details new analysis to illustrate these challenges, based on three significant and contrasting deltas: the Ganges-Brahmaputra-Meghna, Mahanadi and Volta. This multi-disciplinary, policy-orientated volume is strongly aligned to the United Nation's Sustainable Development Goals as delta populations often experience extremes of poverty, gender and structural inequality, variable levels of health and well-being, while being vulnerable to extreme and systematic climate change.